(3GdeSfO GdUMjM GdMSf aj eBKQ CHj GdMSf (B( (3Ydi Hf CHj SYjO GdeQjfi (B)s - (3eMeO Hf CMeO Hf eMeO Hf eQRhb GdYLjSj CHh YHO Gddg , GHf eQRhb , TeS GdOjf,J (B781 (3g` s ((3EHQGgje Hf YeQ GdgTJhci s)
(3ChdgG (B:s
(3GdMeO ddg GdPi eShZ dfG ehGQO fYeg YRHkG RdGdG aGSJNQJ Gddg hUfYJ eNJUQG hLjRkG ai efGbHg GdYGdjI s
(3BNQgG (B:s
(3Gddge EfG fJhSd Edjc HfHjc heLJHGc hMHjHc heUWaGc Cf JJZeO ehdGfG GdeQMhe eYGc s
(3GdfSNI HgG MhGTs
(3HgG JcejdGJ cKjQI ai CeGcf YOI HNW MOjK eZGjQs
(3HgG fXGe GdJYbjHIs
(3LYdg ai ebOeI SJI aUhd s
(3hNeSI hNeSjf HGHkG hNGJeI SHYI aUhd s
(3bQf GdfSN (B:s
Keywords: (3GdJGQjNs